Sentinel Lymph Node Mapping: Current Applications and Future Perspectives in Gynecology Malignant Tumors - Wang, Tianyou; Xu, Yan; Shao, Wenyu; Wang, Chao (Frontiers in Medicine, 2022)
The sentinel lymph nodes (SLNs) is a group of lymph nodes initially involved in the metastatic spread of cancer cells. SLN mapping refers to intraoperative localization and biopsy of SLNs with specific tracers to assess lymph node metastases. It is widely used in a variety of tumor surgeries for its high sensitivity and high negative predictive value. In the evaluation of the status of lymph node metastases in gynecological malignancies, it has received increasingly more attention due to its minor invasiveness, few complications, and high diagnosis rate. The National Comprehensive Cancer Network (NCCN) guidelines provide an excellent introduction to the indications and methods of SLN techniques in vulvar, cervical, and endometrial cancers, but they provide little explanation about some specific issues. In this review, we summarize different dyes and injection methods and discuss the indications of application and the clinical trials of SLN mapping in gynecological malignant tumors, aiming to provide a reference for the rational application of sentinel techniques in gynecology malignant tumors before relevant guidelines are updated.